GADEN: a 3D gas dispersion simulator for mobile robot olfaction in realistic environments - González-Monroy, Javier; Hernández-Bennetts, Víctor; Fan, Han; Lilienthal, Achim; González-Jiménez, Antonio Javier (MDPI, 2017)
This work presents a simulation framework developed under the widely used Robot Operating System (ROS) to enable the validation of robotics systems and gas sensing algorithms under realistic environments. The framework is rooted in the principles of computational fluid dynamics and filament dispersion theory, modeling wind flow and gas dispersion in 3D real-world scenarios (i.e., accounting for walls, furniture, etc.). Moreover, it integrates the simulation of different environmental sensors, such as metal oxide gas sensors, photo ionization detectors, or anemometers. We illustrate the potential and applicability of the proposed tool by presenting a simulation case in a complex and realistic office-like environment where gas leaks of different chemicals occur simultaneously. Furthermore, we accomplish quantitative and qualitative validation by comparing our simulated results against real-world data recorded inside a wind tunnel where methane was released under different wind flow profiles. Based on these results, we conclude that our simulation framework can provide a good approximation to real world measurements when advective airflows are present in the environment
Keywords: Gases-Análisis; Detectores de gases; Gas dispersal; Robotics olfaction; Gas sensing; Mobile robotics; Robot Operating System (ROS)